Digital Communication Strategy Start-Up Psychology Service Bureau in Improving Consumer Self-Development - Purwaningwulan, Melly Maulin; Rizki, Muhammad Dwi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to determine the Start-Up Digital Communication Strategy of the Psychology Service Bureau in Improving Consumer Self-Development. To answer the objectives of the sub-focus of research includes Defining Communicators, Setting Targets & Analysis of Audience Needs, Composing Messages and Selecting Media & Communication Channels. This study uses a qualitative approach and descriptive research methods. Data collection techniques through in-depth interviews, non-participant observation and documentation. Using purposive sampling technique, 6 informants were obtained. Test the validity of the data using triangulation and member checking. The results of the study show that communicators meet professional criteria in the field of psychology and have a track record as a speaker or motivator. Target audience needs and needs analysis refers to the business model canvas, evaluation results of previous activities and team brainstorming. The nature of the message conveyed is informative and educative. Two-sided issue message delivery techniques and message appeals used rational, emotional and motivational message appeals. Various social media are used to promote program activities and after implementation, YouTube is used as a publication medium. The conclusion of the research is that the Start-Up Digital Communication Strategy of the Psychology Service Bureau has increased the self-development of its consumers, the long-term impact of building psychological social support for the younger generation in dealing with and solving problems.